Karyotype analysis and achiasmatic meiosis in pseudoscorpions of the family Chthoniidae (Arachnida: Pseudoscorpiones) - Stahlavsky, Frantisek; Kral, Jiri (Hereditas, 2004)
Karyotypes of pseudoscorpions (Arachnida, Pseudoscorpiones) are largely unknown. Here we describe for the first time karyotypes of the suborder Epiocheirata, represented by 9 European species of two genera of Chthoniidae, Chthonius and Mundochthonius. Diploid chromosome numbers of males range from 21 to 37. Karyotypes of both genera differ substantially. Acrocentric chromosomes predominate in karyotypes of the genus Chthonius, whereas M. styriacus exhibits a predominance of metacentric chromosomes. These differences suggest that the two genera belong probably to distant branches of the family Chthoniidae. It is proposed that karyotype evolution of the genus Chthonius was characterised by a reduction of chromosome numbers by tandem and centric fusions as well as gradual conversion of acrocentric chromosomes to biarmed ones, mostly by pericentric inversions. A tendency towards reduced chromosome numbers is evident in the subgenus Ephippiochthonius. All species display X0 sex chromosome system that is probably ancestral in pseudoscorpions. The X chromosome exhibits conservative morphology. It is metacentric in all species examined, and in the majority of them, a subterminal secondary constriction was found at one of its arms. In contrast to chthoniids, secondary constriction was not reported on sex chromosomes of other pseudoscorpions. Analysis of prophase I chromosomes in males revealed an achiasmatic mode of meiosis. Findings of the achiasmatic meiosis in both genera, Chthonius and Mundochthonius, indicate that this mode of meiosis might be characteristic of the family Chthoniidae. Amongst arachnids, achiasmatic meiosis has only been described in some scorpions, acariform mites, and spiders.
Keywords: biologická evoluce; diploidie; meióza; Diploidy; chromozomy; Europe; Evropa; karyotypizace; mužské pohlaví; Biological Evolution; Karyotyping; pavoukovci; zvířata; Meiosis; chromozom X; Chromosomes; Species Specificity; druhová specificita; Arachnida; Male; X Chromosome; Animals